ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMK PADA MATERI PROGRAM LINIER - Fakhirah Rizki Wanda Amirah Purwanto; Dani Firmansyah (IKIP Siliwangi, 2022)
The purpose of this research is to describe, document, analyze, and interpret errors made by students in solving mathematical problem solving ability test questions on linear programming material. The approach and method used in this study used a qualitative approach in the descriptive type with 20 students of class XI SMK in the city of Bekasi as the research sample selected using purposive sampling technique. The instrument used in this research is a written test instrument for mathematical problem solving skills with linear programming material in the form of two description questions. The data analysis technique used in this study consisted of data reduction, data presentation, and inference. The indicators used are indicators according to Polya, namely: understanding the problem, making a settlement plan, implementing the plan, and checking the results of the settlement. The results of this study indicate that errors in understanding the problem are the most common and frequently experienced errors, with a percentage of 52%. Errors in making a resolution plan with a percentage of 42%. The error in implementing the plan is with a percentage of 28%. Finally, the error checking the results of the settlement obtained is with a percentage of 26%. The errors made by students are mostly on indicators of understanding the problem. Students are less able to understand the questions on linear programming material so that students experience many errors in planning problem solving.